Are Men’s Reproductive Health Problems and Sexual Behavior Predictors of Welfare? - Emmanuel O. Amoo PhD; Gholahan A. Oni PhD; Mofoluwake P. Ajayi PhD; Adenike E. Idowu PhD; Theophilus O. Fadayomi PhD; Adekunbi K. Omideyi PhD (American Journal of Men's Health, 2017)
The study examined men’s reproductive health problems and sexual behavior and their implications for men’s welfare in Nigeria. It used the Nigeria Demographic and Health Survey data set of 2013. The analysis used only male recode files, representing 17,359 males. The dependent variable is the computed wealth index, which was selected as proxy for welfare condition. Analysis involved univariate and multivariate levels. The findings indicated that 49.3% of the respondents currently have more than one sexual partner. The total lifetime sexual partner index identifies 70.2% of the men interviewed have had at least two sexual partners in their lifetime. It revealed that men who experience reproductive health challenges, such as sexually transmitted infections and genital ulcer, are 44% and 93%, respectively, less likely to enjoy good welfare condition. It also indicated that men in urban area are 7.256 times more likely to enjoy good welfare condition compared with their rural counterparts. There is a negative association between total lifetime sexual partnerships and exposure to good welfare. The study concludes that social workers, marriage counselors, other health personnel, and policy makers need to focus on the practice of multiple sexual partnership and reproductive health diseases as major determinants of men’s welfare. The authors suggest that the index of welfare should include reproductive health issues and indicators of sexual behavior. Also, there is need for the establishment of specialized reproductive health care services and centers that are accessible to all men for effective servicing of reproductive health needs of men in the country.